Lacticaseibacillus rhamnosus LRa05 in the treatment of acute diarrhea in children: a randomized controlled trial - Chen, Ke; Zeng, Kaihong; Jin, Shanshan; Ma, Yu; Cai, Limei; Xu, Ping; Nie, Yang; Luo, Li; Yu, Qinghua; Liu, Changqi (Frontiers in Nutrition, 2024)
The goal of this study is to assess the efficacy and safety of Lacticaseibacillus rhamnosus LRa05, as an adjunct to the treatment of acute watery diarrhea in children. Eligible diarrheal children were randomized into intervention group (IG, n=57) and control group (CG, n=54), and given probiotics or placebo, respectively. The total duration of diarrhea in the IG (121.4±13.7 h) was significantly shorter than that in the CG (143.9 ± 19.8 h, p <0.001). More children in the IG showed improvements in diarrhea than those in the CG for both per protocol analysis (70.2% vs 46.3%, p=0.01) and intention-to-treat analysis (66.7% vs. 41.7%, p=0.003). The LL-37 levels in the IG was markedly higher than that in the CG after the intervention (4349.35±1143.86 pg/g vs. 3682.49±869.21 pg/g, p=0.039). The intervention led to higher abundance of Bifidobacterium longum and lower abundance of Enterococcus faecium, Lactobacillus rhamnosus, and Bacteroides fragilis (p<0.05). LRa05 treatment upregulated the functional genes of gut microbiota involving immunity regulation. Administration of the Lacticaseibacillus rhamnosus LRa05 at a dose of 5×10 9 CFU/day to children aged 0-3 years resulted in shorter duration of 3 3 diarrhea, faster improvement in fecal consistency, and beneficial changes in gut microbiome composition and gene functions.